2010
DOI: 10.1124/jpet.109.162222
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Induction of Cytochrome P4501A1 in Human Hepatoma Cells by 3-Methylcholanthrene: Evidence for Sustained Transcriptional Activation of the CYP1A1 Promoter

Abstract: Cytochrome P450 (P450)1A1 plays a critical role in the metabolic activation and detoxification of polycyclic aromatic hydrocarbons (PAHs), many of which are potent human carcinogens. In this investigation, we tested the hypothesis that MC elicits persistent induction of CYP1A1 expression in human hepatoma cells (HepG2) and that this phenomenon is mediated by sustained transcriptional activation of the CYP1A1 promoter. Treatment of HepG2 cells with MC resulted in marked induction (8 -20-fold) of ethoxyresorufin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…The time-and concentration-dependent induction of luciferase activity by 3MC was clearly observed in the stable AHRresponsive HepG2 cell line. These effects were comparable to the results obtained using the method for evaluating the CYP1A1 transcriptional activity (Garrison et al 1996;Fazili et al 2010). The difference between transcriptional activity of CYP1A1 and AHRmediated transcriptional activity is not marked when treated with strong AHR-activating compounds such as 3MC.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The time-and concentration-dependent induction of luciferase activity by 3MC was clearly observed in the stable AHRresponsive HepG2 cell line. These effects were comparable to the results obtained using the method for evaluating the CYP1A1 transcriptional activity (Garrison et al 1996;Fazili et al 2010). The difference between transcriptional activity of CYP1A1 and AHRmediated transcriptional activity is not marked when treated with strong AHR-activating compounds such as 3MC.…”
Section: Discussionsupporting
confidence: 73%
“…The correlation between the induction of CYP1A1 mRNA expression and AHR-mediated transcriptional activity is particularly strong in a low concentration range (0.01-1.0 lM). Multiple XREs are located 1,252-892 bp upstream of the CYP1A1 promoter and play an important biological role in regulating CYP1A1 expression (Fujii-Kuriyama et al 1992;Garrison et al 1996;Fazili et al 2010). Conversely, XREs are located approximately 3,424-3,299 bp upstream of the UGT1A1 promoter and 2,357-2,333 bp upstream of the ABCG2 promoter (Yueh et al 2003;Tompkins et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following 24-hour drug exposure, the expression levels of all 3 CYPs were similar to those of the untreated controls (Supplementary Table S2). A previous study has shown that 12 to 24 hours is the optimal time for dose-dependent CYP1A1 induction in HepG2 cells by 3-methylcholanthrene (27). This indicates that ICT2700, at a therapeutically relevant concentration, does not induce expression of the AhR-regulated CYP1 family or adversely affect the CYP1A1 levels required for its oxidative conversion to a potent cytotoxin.…”
Section: Lack Of Induction Of Cyp1 Enzyme Expression By Ict2700mentioning
confidence: 98%
“…We also reported that MC elicits sustained CYP1A1 and CYP1A2 induction in vivo via transcriptional activation of the corresponding promoters (Jiang et al, 2009). Furthermore, we showed that MC elicits persistent induction of CYP1A1 in HepG2 cells in vitro by mechanisms entailing sustained transcriptional activation of the CYP1A1 promoter (Fazili et al, 2010).…”
Section: Introductionmentioning
confidence: 67%